(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2024)
Within the first book of Manilius’ Astronomica the exposition of doctrines concerning the Milky Way plays a central role. The poet presents the galaxy as such an eye-catching, luminous object that cannot fail to arouse the viewer’s emotions. Finally, wonder at the sublime spectacle of the galaxy is for Manilius the stimulus that prompts men to inquire about the causes of that celestial phenomenon. This article aims to analyze the relationship between emotion, sublime, and knowledge in the context of Roman culture in the early imperial age. Manilius’ passage is then compared with Chapter 35 of Ps-Longinus’ Treatise on the Sublime, in which the theme of wonder at the grandeur of nature is central. Finally, as a demonstration of the vitality of the link between emotion and knowledge, a comparison is offered between Manilius and Chapter 5 of Seneca’s De otio.